Effect of optimized nitrogen management through conventional and nano-fertilizers on nutrient dynamics and finger millet yield - M. A. Sneha; Mudalagiriyappa; B. G. Vasanthi; K. A. Gopinath; H. S. Latha; K. Devaraja; V. Visha Kumari; D. H. Roopashree; Tarunendu Singh; M. R. Krupashankar; Vinod Kumar Singh (Frontiers in Nanotechnology)
Nitrogen and zinc nutrition significantly influence crop productivity. Foliar application, especially using nano-nitrogen and nano-zinc, enhances nutrient use efficiency and rapidly corrects deficiencies, offering a promising approach to improve crop growth and performance alongside conventional fertilization practices. The present study was undertaken to assess the nutrient dynamics in finger millet (GPU-28). A field experiment was taken up at AICRPDA centre, Bengaluru for two seasons during rainy season (kharif) Kharif 2021 and 2022 in a factorial randomized complete block design replicated thrice. Treatments included four levels of nitrogen - N1: No nitrogen, N2: 50% of the recommended dose of nitrogen (RDN: 25 kg N ha-1), N3: 75% RDN (37.5 kg N ha-1) and N4: 100% RDN (50 kg N ha-1); and four modes of fertilizers application - F1: Soil application of zinc, F2: Foliar spray of nano-nitrogen, F3: Foliar spray of nano-zinc and F4: Foliar spray of nano-nitrogen and nano-zinc along with two control treatments (Control-1: Recommended PK, Control-2: Recommended NPK). Nano-fertilizers were applied twice at 35 and 55 days after sowing (DAS) @ 2 mL L-1 and all treatments received recommended doses of phosphorus (40 kg P2O5 ha-1) and potassium (37.5 kg K2O ha-1). Additionally, a complementary pot culture study was conducted to evaluate physiological responses of finger millet to nano-fertilizers under controlled conditions, which corroborated the field results. Application of 100% RDN combined with foliar sprays of nano-nitrogen and nano-zinc resulted in significantly higher grain yield (3453 kg ha-1), uptake of nitrogen, phosphorus, potassium and zinc at all growth stages, which was comparable to the application of 75% RDN along with the same foliar applications of nano nutrients. Furthermore, higher nitrogen use efficiency was noticed with application of 75% RDN along with the foliar application of nano-N and nano-Zn. The nutrient balance study further confirmed that 75% RDN combined with nano fertilizers led to lower nitrogen losses compared to 100% RDN, indicating better nutrient use efficiency (NUE) and reduced environmental risks. In conclusion, applying 75% RDN combined with the recommended PK along with foliar application of nano-nutrients, demonstrates significant potential for efficient nutrient management.